On the challenging problem to estimate the energy of the Ultra High Energy Cosmic Rays - Verzi Valerio (EPJ Web of Conferences)
Ultra High Energy Cosmic Rays (UHECRs) are rare nuclei that collide in the atmosphere with energy larger than 1018 eV. In this contribution we critically review the experimental techniques for estimating their energy, trying to address current limitations and potential improvements that can be developed in the coming years.